Nigeria - State Level Public Expenditure Management and Financial Accountability Review : A synthesis Report - World Bank (Washington, DC, 2013)
This report synthesizes the findings of public expenditure management and financial accountability reviews (PEMFARs) that were conducted in seven states between 2008 and 2009. The states covered were Anambra, Bayelsa, Ekiti, Kogi, Niger, Ondo, and Plateau. The report seeks to analyze and summarize the key findings of the reviews from these states in order to ensure that the key messages from the otherwise voluminous reports are presented in a single, smaller report. The states have different socio-economic characteristics but all operate in a federal system that offers some reasonable operational autonomy in the context of a federal constitution. Under the federal system of government, states have been allocated significant responsibilities for service delivery. The constitution defines the expenditure and revenue collection responsibilities that are under their purview. To carry out their responsibilities, the Public Financial Management (PFM) institutional framework is modeled after that of the federal government. All three branches of government are in place with the executive governor as head of state administration. Given the relative autonomy that states enjoy, each state prepares and implements its own budget. Like the federal government, the framework for state PFM system is therefore defined by the budget process.